(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Sulu economy is not stable as it cannot meet the growing demands of the local people. The mode of production is backward and the means of production are further crippled by riba, and lack of infrastructure facilities. The objectives of this study are as follows: 1). To know the present state of the Sulu economy, 2). To assess the halal industry as an approach to stimulate economic growth and 3). To identify the role of the ulama and the local governments. Methodology of this study is based on descriptive method. The research instruments used to generate data are focus group discussion, interview, community immersion, and library works. Halal industry is largely pointed by the FGD participants as the most potential factor to stimulate economic growth in Sulu. The way to realize this is that the local government must invest in infrastructure development such as roads, water facilities, standard slaughterhouse, electricity and internet connection and initiate the establishment of the Islamic bank. Halal certifying board must be established and must be manned by scientists, ulama, and management experts. The board will regulate food industry and tourism. The findings also pointed out the role of the ulama is to educate business people about riba, the concept of halal and Islamic finance such as mudaraba, musharaka and murabaha. The ulama, the leaders and the masses are the pillars of the Sulu economy. The ulama hold the key to moral governance. The role of the local government is to improve the physical facilities such as road networks, electricity, internet connection, delivery of basic services and to maintain peace and order and security of the people. It is the masses who will organize industry, exploit the resources and implement development.